'Dropped from the system': the experiences and challenges of long‐term breast cancer survivors. (13th January 2017) - Matthews, Hannah; Semper, Heather
Abstract: Aims: The aim of this study was to explore breast cancer patients' experiences during survivorship. Particular attention is given to the role of specialist breast care nurses in supporting women throughout this phase. Background: There is a relative lack of research involving long‐term breast cancer survivors. Yet, many survivors experience substantial psychosocial and iatrogenic harms created by diagnosis, symptoms of disease and treatment. A more comprehensive understanding may assist in supporting the needs of breast cancer survivors. Design: An exploratory qualitative approach was used to collect data on breast cancer survivors' experiences during 2013. Methods: Semi‐structured interview data were collected from seven British women aged 38–80 years exploring the support received during survivorship. Data were analysed using Interpretive Phenomenological Analysis. Findings: Breast cancer survivors perceived a systemic absence in support from oncology teams and rapid deterioration of support from personal support networks. Despite this, survivors were able to find benefits from the cancer experience. This allowed for adjustment and enabled patients to assume a new identity as a breast cancer survivor. We recommend specialist breast care nurses would be suitably placed to provide extended support allowing for a salient transition from treatment to survivorship. Conclusion: This study yields insights into breast cancer survivorship and specifically the role of specialist breast care nurses. Given the growing cohort of breast cancer survivors and the increased importance on promoting and supporting optimal psychosocial adjustment, we advise the cost‐effectiveness of providing continuing nursing support and the mode of administration requires further research.